„Tisztelt Nagysád!” Társadalmi kapcsolatok és nyomtatott periodikák jelentősége a magyar feminista mozgalomban a századelőn A Nő című folyóirat szerkesztői levelezése nyomán - Acsády, Judit (Per Aspera ad Astra, 2020)
The Association of Feminists (founded in 1904 in Budapest by Vilma Glücklich and Rózsa Schwimmer) was one of the social organizations being active in the flourishing civil life of the turn of the century in the Austro–Hungarian Monarchy. The organizations played an active life in the reform processes and in the articulation of the interests of different social groups. Schwimmer Rózsa proposed to launch a feminist periodical as the journal of their own movement. Woman and Society came out in 1907 as the bulletin of two organizations, the Association of Feminists and the National Association of Women Clerks. The editors were conscious of the importance of spreading the ideas of the movement and reaching a wider circle of supporters. As a social movement periodical The Woman and Society served its function to create an alternative public space for feminist ideas. The editors of the Hungarian feminist journal were in connection with the editorial board of the Jus Suffragii and exchanged the news of the international women’s movements. The periodical of the Feminist Association in Budapest changed its title in 1914 to The Woman. Feminist Journal. It appeared as a fortnightly with a different layout, including more illustrations and also black and white photographs. The journal since then gained an increasing interest and became spread to many different parts of the country. It also had subscribers abroad. The recent study examines the network of subscribers on the base of the archival source of the letters to the editors. The correspondence is also suitable for the examination of the editors’ strategies to disseminate the journal and reaching an even wider public of readers for their case of women’s emancipation. Fotó: Országos Széchényi Könyvtár